Combining explicit instruction and positive psychology to see adolescents with learning difficulties flourish. Issue 2 (2nd July 2020) - White, Matthew Oliver
ABSTRACT: Academically engaging adolescents with learning difficulties continues to be a challenge for teachers and education authorities around the world. This paper reports on one part of a broader study to address the impasse present between research and practice in meeting the needs of adolescents with learning difficulties. Drawing on the mounting research attesting to the effectiveness of Explicit Instruction and Positive Psychology, a concerted investigation was carried out to assess the effectiveness of combining the two approaches. Two Year 8 classes (N = 23 experimental) (English and Mathematics) were provided with the combined systems intervention over one academic year. Response to the intervention was compared to two similar academic ability control groups from the same Year group. Results report students made statistically significant gains, in comparison to the control group. This study contributes to an understanding of how effective classroom pedagogy instead of remediation can support adolescents with learning difficulties.